A song for you [compact disc] - Evans, Luke, 1979- (BMG, 2022)
Luke Evans returns with his upcoming album including twelve beautiful covers and two original tracks. The originals 'Busy Breaking Yours' and 'Horizons Blue' are the first tracks Evans has written to be released and are co-writes with Amy Wadge, one of the UK's most successful contemporary songwriters.